The influence of fabrication parameters on the electrochemical performance of multifunctional structural supercapacitors. Issue 3 (31st August 2021) - Qi, Guocheng; Nguyen, Sang; Anthony, David B; Kucernak, Anthony R J; Shaffer, Milo S P; Greenhalgh, Emile S
Abstract: Multifunctional structural supercapacitors based on carbon fibre electrodes (CF) and structural electrolytes (SEs) can realise multifunctionality by simultaneously bearing load and providing electrochemical energy storage. Structural supercapacitor constituents (i.e. electrodes and electrolytes) have undergone significant development to enhance their electrochemical and mechanical properties. However, the fabrication of fully functional devices presents a number of practical challenges to achieve optimal multifunctional properties, particularly those associated with assembly and lamination. This work investigated the effect of separator selection and processing parameters on the electrochemical performance of structural supercapacitors, as well as evaluating the repeatability of the SE filming process. Two layers of glass fibre fabrics were the most effective separator for preventing short-circuiting of the structural supercapacitors. The weight fraction of the SE matrix had a significant effect on the capacitance, energy and power of the structural supercapacitors. By addressing such fabrication challenges, high performance structural supercapacitors can be manufactured with greater reproducibility and at larger scales such that they are suitable for integration in industrial applications.